Assessing the Effectiveness of Collaborative SubjectSpecific Library Instruction - Nielsen, Jordan; Jetton, Lora Lennertz (Qualitative and Quantitative Methods in Libraries; Vol 3 No 1 (2014): March 2014 Issue, 2017)
In the fall semester of 2012, the communications librarian and the business librarian at the University of Arkansas began working together to provide collaborative library instruction. The librarians collaborated on instruction for Communication 1313, a course that focuses on the fundamentals of public speaking. Due to the course being a requirement for business majors, many sections of the course were made up entirely of business students. The business sections were identified, and the librarians worked together to provide instruction to these sections. The instruction sessions included general library information, and information about communications and business resources. In the spring of 2013, the librarians will once again work together to provide instruction to business students taking Communication 1313. Through the use of surveys, the librarians will determine how effective their collaboration efforts were. The librarians plan to look at the perceptions the students have about performing library research at the beginning of the semester, and they plan to see how those perceptions have changed by the end of the semester.